2011
DOI: 10.1161/atvbaha.110.206375
|View full text |Cite|
|
Sign up to set email alerts
|

Novel Function of Tenascin-C, a Matrix Protein Relevant to Atherosclerosis, in Platelet Recruitment and Activation Under Flow

Abstract: Objective-The identification of platelet-reactive proteins exclusively present in atherosclerotic plaques could provide interesting targets for effective and safe antithrombotic strategies. In this context, we explored platelet adhesion and activation to tenascin-C (TN-C), a matrix protein preferentially found within atheroma. Methods and Results-We show that platelets efficiently adhere to TN-C under both static and flow conditions.Videomicroscopy revealed a unique behavior under flow, with platelets exhibiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 22 publications
1
32
0
Order By: Relevance
“…They went on to show that ␣2␤1 and ␣V␤3 integrins could be eluted from a tenascin-C affinity column, and that these two integrins bound to tenascin-C in a solid-phase assay. More recently, Schaff et al (2011) showed that platelets attach well to tenascin-C in an ␣2␤1-dependent manner, implicating a role for tenascin-C in hemostasis. In addition to ␣V␤3, ␣8␤1 integrin may also bind to the RGD in the FN3-3 of tenascin-C. Schnapp et al (1995) expressed ␣8 integrin in ␤1-expressing 293 cells (from human embryonic kidney) and showed that they bind to chicken tenascin-C and chicken tenascin-C FN3-3 in an RGD-dependent manner that is blocked with antibodies to ␤1 integrin.…”
Section: Tenascin-c As An Integrin Ligandmentioning
confidence: 99%
“…They went on to show that ␣2␤1 and ␣V␤3 integrins could be eluted from a tenascin-C affinity column, and that these two integrins bound to tenascin-C in a solid-phase assay. More recently, Schaff et al (2011) showed that platelets attach well to tenascin-C in an ␣2␤1-dependent manner, implicating a role for tenascin-C in hemostasis. In addition to ␣V␤3, ␣8␤1 integrin may also bind to the RGD in the FN3-3 of tenascin-C. Schnapp et al (1995) expressed ␣8 integrin in ␤1-expressing 293 cells (from human embryonic kidney) and showed that they bind to chicken tenascin-C and chicken tenascin-C FN3-3 in an RGD-dependent manner that is blocked with antibodies to ␤1 integrin.…”
Section: Tenascin-c As An Integrin Ligandmentioning
confidence: 99%
“…15,16 Although some controversies persist, the role of integrin ␣2␤1 in adhesion to collagen, platelet activation, and thrombus formation is well documented. 14,[17][18][19] Recruitment of integrin ␣2␤1 initiates an outside-in signaling pathway leading to platelet spreading on the extracellular matrix and to activation of integrin ␣IIb␤3, thus allowing binding of soluble fibrinogen to adherent platelets.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Schaff et al discovered that thrombocytes interact with TN-C through von-Willebrand factor and the adhesion that occurs via that interaction subsequently triggers thrombocyte activation [22].…”
Section: Discussionmentioning
confidence: 99%